1987
DOI: 10.1002/ajpa.1330740404
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric analysis of the face in hypohidrotic ectodermal dysplasia: A family study

Abstract: Sixteen individuals with hypohidrotic ectodermal dysplasia (HED) were compared to normal standards as well as to 16 unaffected family members by using a series of 20 anthropometric measurements of the head and face. Individuals with HED were generally smaller than normal controls or their unaffected relatives. However, this size reduction was not uniform. Instead, it was most evident in the anterior-posterior dimensions of the lower two-thirds of the face, in facial height, and in the size of the ears, nose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 10 publications
3
51
1
Order By: Relevance
“…Syndrome-specific patterns are being compiled in Sotos syndrome [Allanson and Cole, 19921, Wiedemann-Beckwith syndrome (Ward et al, 1990;Hunter and Allanson, 19931, Simpson-GolabiBehmel syndrome [Hughes-Benzie et al, 19921, hypohidrotic ectodermal dysplasia [Ward and Bixler, 19871, and Williams syndrome (Pober B, personal communication). These are being used not only for diagnosis of affected individuals but also for identification of carriers [Ward and Bixler, 1987;Hughes-Benzie et al, 19921.…”
Section: Discussionmentioning
confidence: 99%
“…Syndrome-specific patterns are being compiled in Sotos syndrome [Allanson and Cole, 19921, Wiedemann-Beckwith syndrome (Ward et al, 1990;Hunter and Allanson, 19931, Simpson-GolabiBehmel syndrome [Hughes-Benzie et al, 19921, hypohidrotic ectodermal dysplasia [Ward and Bixler, 19871, and Williams syndrome (Pober B, personal communication). These are being used not only for diagnosis of affected individuals but also for identification of carriers [Ward and Bixler, 1987;Hughes-Benzie et al, 19921.…”
Section: Discussionmentioning
confidence: 99%
“…(9) also reported that children with ED, in general, had lower body mass index (BMI) than normal children, but no specific data for HED were presented. Ward and Bixler (10) observed that the head circumference was reduced in HED.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the small sample size of the male twins, the anthropometric battery was broken down into linear measurements, head and face measures, and breadth dimensions for the purpose of the study. This (Ward and Bixler, 1987;Rudan et al, 1986); odontometry (Boklage, 1987;Sofaer et al, 1986); dermatoglyphics (Dow et al, 1987;Arrieta et al, 1987); genetic polymorphisms (Wood, 1986;Chakraborty et al, 1986;Hitzeroth, 1986); or comparisons of distance matrices based upon two or more types of variables (Reddy et al, 1987;Rudan et al, 1987;Kobyliansky and Livshits, 1986). In the case of genetic polymorphisms, the distance calculated between groups is a summary estimate of their gene and genotypic frequency differences.…”
Section: Methodsmentioning
confidence: 98%